Ambiguous Survival Beliefs and Hyperbolic Discounting in a Life-Cycle Model - Max Groneck; Alexander Ludwig; Alexander Zimper (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2013)
On average, young people underestimate whereas old people overestimate their chances to survive into the future. We employ a subjective survival belief model proposed by Ludwig and Zimper (2013), which can replicate these patterns. The model is compared with hyperbolic discounting within a standard life-cycle setting of consumption and savings. We show theoretically that the first order conditions of our ambiguous survival belief model closely resemble the generalized Euler-equation from the hyperbolic discounting model with an additional adjustment factor. In the numerical section it is shown that the subjective survival belief model simultaneously leads to undersaving at younger ages and high asset holdings and little dissaving of the elderly. The model can thus replicate two important empirical facts of the life-cycle literature at once which is not possible with a hyperbolic discounting model.
Keywords: D91; E21; D83; 330